2018
DOI: 10.1002/hyp.13127
|View full text |Cite
|
Sign up to set email alerts
|

Data assimilation in groundwater modelling: ensemble Kalman filter versus ensemble smoothers

Abstract: Groundwater modelling calls for an effective and robust data integrating method to fill the gap between the model and observation data. The ensemble Kalman filter (EnKF), a real‐time data assimilation method, has been increasingly applied in multiple disciplines such as petroleum engineering and hydrogeology. In this approach, a groundwater model is updated sequentially with measured data such as hydraulic head and concentration. As an alternative to the EnKF, the ensemble smoother (ES) has been proposed for u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…van Leeuwen and Evensen (van Leeuwen and Evensen 1996) proposed a variant of EnKF: ensemble smoother (ES). It has been shown that ES can obtain similar results to EnKF but with a much lower computational cost (Li et al 2018), and widely used in hydrogeology and reservoir research (Bailey and Baù 2010;Bailey et al 2012;Lima et al 2020). But when the system is highly nonlinear, iterative application of ES (IES) are needed (Chen and Oliver 2012).…”
Section: Introductionmentioning
confidence: 99%
“…van Leeuwen and Evensen (van Leeuwen and Evensen 1996) proposed a variant of EnKF: ensemble smoother (ES). It has been shown that ES can obtain similar results to EnKF but with a much lower computational cost (Li et al 2018), and widely used in hydrogeology and reservoir research (Bailey and Baù 2010;Bailey et al 2012;Lima et al 2020). But when the system is highly nonlinear, iterative application of ES (IES) are needed (Chen and Oliver 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Ensemble methods like IES have been referred to as “derivative free” methods (Kovachki and Stuart 2019) for data assimilation because they rely on an approximate gradient between parameters and observations generated using Monte Carlo, whereas traditional approaches require a minimum of one forward model run for every perturbed parameter as well as one run for the base parameter set to construct the Jacobian sensitivity matrix used to determine a parameter upgrade; IES uses empirical correlations from a Monte‐Carlo style ensemble to build an approximate Jacobian matrix (Li et al 2018; Yu et al 2020). Large efficiencies can be realized because filling this approximated Jacobian matrix is based on the number of user specified realizations rather than the number of parameters (Chen and Oliver 2013; White 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their Monte Carlo nature, ensemble‐based methods are easy to implement and are becoming increasingly popular in subsurface data assimilation (Emerick & Reynolds, 2013; L. Li et al., 2018; Panzeri et al., 2013; Skjervheim & Evensen, 2011). To guarantee performance, a relatively large ensemble size is usually required.…”
Section: Introductionmentioning
confidence: 99%